Praktiese kerkwees in die nuwe Suid-Afrika - Dreyer, T. F. J. (Hervormde teologiese studies, 1996)
The praxis of the church in the new South Africa. Political and social changes in the new South Africa will impose a new praxis with far reaching consequences, especially for the Afrikaans speaking churches. Although it is still premature to definethe new praxis the church has to be prepared to accept the challenges. A few studies in this regard have already been published. This paper is an attempt to draw certain guidelines, based on available research done in this area.